2022
DOI: 10.3389/fphar.2022.826404
|View full text |Cite
|
Sign up to set email alerts
|

Mammea B/BA Isolated From the Seeds of Mammea americana L. (Calophyllaceae) is a Potent Inhibitor of Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus remains a pathogen of high concern in public health programs worldwide due to antibiotic resistance and emergence of highly virulent strains. Many phytochemicals have demonstrated activity against S. aureus and other Gram-positive bacteria, but the minimum inhibitory concentration (MIC) values comparable to commonly used antibiotics are needed. In the present study, bio-guided fractionation of the ethanol extract of seeds of Mammea americana L. (Calophyllaceae) throughout the antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Manjulatha [ 36 ] mentioned an MBC ranging from 125 μ g/mL to 500 μ g/mL using the ethanolic seed extracts of M. americana against Streptococcus mutans ATCC 25175 (gram-positive bacteria). Similarly, Pajaro-Gonzalez et al [ 12 ] report MBC higher than 64 μ g/mL (>64 μ g/mL) establishing in their investigation a bacteriostatic effect of the extract. Interestingly, the ethanolic extract of the aerial part of M. americana presented greater activity against S. epidermidis strains (91 μ g/mL to 540 μ g/mL) followed by the MBC of isolated and ATCC strains of S. aureus (625 μ g/mL and 650 μ g/mL, respectively) and finally by S. saprophyticus (1750 μ g/mL).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Manjulatha [ 36 ] mentioned an MBC ranging from 125 μ g/mL to 500 μ g/mL using the ethanolic seed extracts of M. americana against Streptococcus mutans ATCC 25175 (gram-positive bacteria). Similarly, Pajaro-Gonzalez et al [ 12 ] report MBC higher than 64 μ g/mL (>64 μ g/mL) establishing in their investigation a bacteriostatic effect of the extract. Interestingly, the ethanolic extract of the aerial part of M. americana presented greater activity against S. epidermidis strains (91 μ g/mL to 540 μ g/mL) followed by the MBC of isolated and ATCC strains of S. aureus (625 μ g/mL and 650 μ g/mL, respectively) and finally by S. saprophyticus (1750 μ g/mL).…”
Section: Resultsmentioning
confidence: 86%
“…Regarding this, a significant number of reports highlight the biological activities of M. americana , such as potential source of natural antioxidants, antimicrobial and even for the treatment of skin diseases [ 10 , 11 ]). Furthermore, a recent study by Pajaro-Gonzalez et al [ 12 ] reported antibacterial activity at low concentrations of the ethanol extract of the seeds of M. americana against S. aureus (ATCC and clinical) strains that are sensitive and resistant to methicillin. Regarding D. viscosa , several reports of its antibacterial activity can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Schneid 0.5–8 μg/mL against Gram-positive bacteria, 2 μg/mL E . coli, < 1 μg/mL against M. smegmatis [ 69 , 70 ] 4 Mammea B/BA Mammea americana L. 0.5–1 μg/mL against methicillin-sensitive and methicillin-resistant S. aureus strains [ 74 , 77 ] 5 Cannabinoids (e.g., cannabidiol, cannabigerol) Cannabis sativa L. 1–4 μg/mL against MRSA , multi-drug resistant Streptococcus pneumoniae, Enterococcus faecalis , and Clostridioides difficile [ 85 , 86 ] 6 27- epi -Scutianine N Scutia buxifolia Reissek 1.56 μg/mL against Enterobater aerogenes [ 126 ] 7 Berberine Hydrastis canadensis. L , Coptis chinensis Franch.…”
Section: Plants As Potential Source Of New Antibacterial Agentsmentioning
confidence: 99%
“…Coumarins in the genus Mammea have been chemically categorized into 4-(phenyl)coumarins, 4-(alkyl)coumarins and 4-(1-acetoxypropyl)coumarins [ 76 ]; Mammea B/BA is a 4-(alkyl)coumarin. In a recent bio-guided fractionation study, Pájaro-González et al (2022) reported the isolation of mamey coumarin-type Mammea B/BA from the ethanol seed extract of Mammea americana (mamey), and its anti- Stapylococcal activity [ 77 ].…”
Section: Plants As Potential Source Of New Antibacterial Agentsmentioning
confidence: 99%
See 1 more Smart Citation